The informational system model of Ukrainian national transport workflow improvement based on electronic signature introduction management - Grigoriy NECHAEY (Transport Problems, 2007)
Proposed model of informational system supposes improvement of newconceptual method on the work with e-signature in transport nformational systems. Problems and aims that may be solved with the help of this system and the most important economical and technical advantages of the proposed system in comparison with traditional methods of e-signing use are marked out.